A Sorrow Shared Is a Sorrow Halved: Moral Judgments of Harm to Single versus Multiple Victims - Konis, Daffie; Haran, Uriel; Saporta, Kelly; Ayal, Shahar (Frontiers in Psychology, 2016)
We describe a bias in moral judgment in which the mere existence of other victims reduces assessments of the harm suffered by each harmed individual. Three experiments support the seemingly paradoxical relationship between the number of harmed individuals and the perceived severity of the harming act. In Experiment 1a, participants expressed lower punitive intentions toward a perpetrator of an unethical act that hurt multiple people and assigned lower monetary compensation to each victim than did those who judged a similar act that harmed only one person. In Experiment 1b, participants displayed greater emotional involvement in the case of a single victim than when there were multiple victims, regardless of whether the victims were unrelated and unaware of each other or constituted a group. Experiment 2 measured the responses of the victims themselves. Participants received false performance feedback on a task before being informed that they had been deceived. Victims who were deceived alone reported more negative feelings and judged the deception as more immoral than did those who knew that others had been deceived as well. Taken together, these results suggest that a victim’s plight is perceived as less severe when others share it, and this bias is common to both third-party judges and victims.